Competencias laborales de los tripulantes en el departamento de restaurante del crucero Costa Luminosa: Working Skills Of The Crew In The Restaurant Department Of Costa Luminosa Cruise Ship - Arias Gonzáles, José Luis; Rodríguez Valeriano, Andrea (CIMEXUS, 2023)
El presente artículo científico tuvo como objetivo principal identificar las competencias laborales de los tripulantes en el departamento de restaurante del crucero Costa Luminosa, se realizó un estudio con alcance descriptivo, diseño no experimental – transversal, de noviembre del año 2019 a marzo del año 2020, el crucero tuvo un itinerario de Italia a Estados Unidos. La población y muestra se conformó por 146 tripulantes camareros tripulantes. La técnica utilizada fue la observación directa y el instrumento fue la escala PIAAC: Evaluación de Competencias de Adultos (Programme for the International Assessment of Adult Competencies International Survey of Adult Skills). Se concluyó que, los tripulantes del departamento de restaurante del crucero Costa Luminosa presentaron un alto nivel en las siguientes competencias laborales: sensibilidad interpersonal, orientación al cliente, persuasión e influencia y consciencia organizativa. Abstract The main objective of this scientific article was to identify the labor competencies of the crew in the restaurant department of the cruise ship Costa Luminosa, a study with a descriptive scope, non-experimental design - transversal was carried out, from November 2019 to March 2020, the cruise had an itinerary from Italy to the United States. The population and sample was made up of 146 crew waiters crew members. The technique used was direct observation and the instrument was the PIAAC scale: Adult Skills Assessment (Program for the International Asse ssment of Adult Competencies International Survey of Adult Skills). It was concluded that the crew of the restaurant department of the Costa Luminosa cruise ship presented a high level in the following job competencies: Interpersonal sensitivity, customer orientation, persuasion and influence, organizational awareness.